2010
DOI: 10.3945/ajcn.2010.29870
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of malabsorption to the reduction in net energy absorption after long-limb Roux-en-Y gastric bypass

Abstract: Background: Roux-en-Y gastric bypass (RYGB) restricts food intake, and when the Roux limb is elongated to 150 cm, the procedure is believed to induce malabsorption. Objective: Our objective was to measure total reduction in intestinal absorption of combustible energy after RYGB and the extent to which this was due to restriction of food intake or malabsorption of ingested macronutrients. Design: Long-limb RYGB was performed in 9 severely obese patients. Dietary intake and intestinal absorption of fat, protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(114 citation statements)
references
References 36 publications
5
105
1
3
Order By: Relevance
“…Despite the rapid pouch emptying, the overall absorption of glucose has been reported to be largely unaffected after RYGB at 1 year, and comparable with normal subjects (9). These observations attest to the importance of the "restrictive component" of RYGB in triggering and maintaining weight loss (6)(7)(8).…”
Section: Obesity Biology and Integrated Physiologysupporting
confidence: 55%
See 1 more Smart Citation
“…Despite the rapid pouch emptying, the overall absorption of glucose has been reported to be largely unaffected after RYGB at 1 year, and comparable with normal subjects (9). These observations attest to the importance of the "restrictive component" of RYGB in triggering and maintaining weight loss (6)(7)(8).…”
Section: Obesity Biology and Integrated Physiologysupporting
confidence: 55%
“…While the mechanisms underlying the effects of RYGB on body weight are incompletely understood, the anatomical alterations are thought to reduce oral intake via the restrictive gastric pouch, nutrient malabsorption and neurohormonal changes arising from the intestinal "short circuit" that favor weight loss, and improved glycemic control (3)(4)(5). It has been suggested that weight loss following RYGB is predominantly due to restricted food intake (79%) and malabsorption (11%), particularly malabsorption of fats (40% reduction) (6)(7)(8). Surprisingly, carbohydrate absorption is not significantly altered following RYGB in humans, despite accelerated emptying of the gastric pouch and accelerated intestinal transit (9), and the underlying reasons are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Extreme caloric restriction to the limit just tolerated in patients after surgery improved insulin resistance in obese subjects similarly as found in after the first week after RYGB (5). Of interest, the malabsorptive component of the RYGB procedure approximately accounts only for up to 11% of the total reduction in combustible energy absorption (6). Changes of adipokine-induced inflammation and insulin resistance (7) and reduction of branched-chain amino acids correlating with insulin resistance (8) have been proposed as further mechanisms operating after bariatric surgery complementing the sole weight loss.…”
mentioning
confidence: 93%
“…The highly variable degree of secondary hyperoxaluria may be due to differences in protein, lipid, calcium, and oxalate intake from other studies. However, only a handful of studies have reported dietary patterns (8,9,11,35). The present pattern of low protein intake by post-BS patients, evidenced by the food recalls and the lower urea, uric acid, and creatinine excretion, may have interfered with our rates of hyperoxaluria (36,37).…”
Section: Discussionmentioning
confidence: 96%